Complexidade estrutural e composição química das macroalgas como fatores estruturantes da fauna associada - Fernandes, Felipe de Oliveira (2021)
Seaweeds play several roles for associated fauna. In this context, this work was divided into three chapters to investigate how the structural complexity of different seaweeds may affect ecological aspects of the associated fauna (richness, density, diversity and composition) and which role seaweed complexity and chemical composition play on habitat and food choice by their fauna as well as predation. In the first chapter, the influence of seaweed structural complexity was analyzed based on ecological aspects of the fauna associated with six species of seaweeds. The ecological aspects were evaluated considering the fractal area (spaces between branches), the fractal perimeter (contour level) and the volume of seaweeds. Seaweeds differed in both morphological traits and structural complexity. Species richness and density depended on seaweed structural complexity. In the second chapter, experiments were carried out to assess the choices (food, habitat and chemical cues) by amphipods concerning different species of seaweeds. Gracilaria cervicornis was the most consumed seaweed among the species offered. Moreover, in the experiments of chemical cues (mimics with and without algal extracts), the amphipods were attracted only by those with extracts of G. cervicornis. These results indicate that amphipods are likely attracted by chemical cues from G. cervicornis as they serve primarily as a food source. In the third chapter, experiments were carried out to determine whether the seaweed choice by amphipods is influenced by predators based on chemical cues. The animals preferred D. delicatula cues over those of G. cervicornis and G. coarctatum. The amphipods also selected more G. cervicornis cues than those of G. coarctatum. When predator cues were mixed with D. delicatula cues, amphipods changed their initial choice for G. cervicornis. However, when predator cues were added to G. cervicornis, the animals maintained their preference for this seaweed’s cues over those of G. coarctatum. These results demonstrate that, although they prefer some seaweeds, amphipods are able to adapt their behavior based on predator chemical cues.